Effect of Pt introduced on Ru-based electrocatalyst for oxygen evolution activity and stability - Jaekyung Yi (Electrochemistry Communications, 2019)
Ru-based electrocatalysts are generally known to be suitable for the oxygen evolution reaction (OER), but they have intrinsic problems in balancing catalytic activity and stability. In this study, we took the strategy, introducing Pt atoms into the structure of crystalline RuO2 to enhance the catalytic property toward OER while maintaining durability. The OER activity of Ru0.9Pt0.1O2/C with high stability was significantly higher than that of RuO2/C. In situ/operando ICP-MS analysis showed that Ru dissolution of Ru0.9Pt0.1O2/C during OER was suppressed by introducing Pt and thermal treatment when compared to Ru/C. The XPS results after OER measurement indicated that the Ru oxidation state of Ru0.9Pt0.1O2/C was higher than that of RuO2, which led to high OER catalytic activity. Based on these results, we hypothesize that the enhanced OER activity of Ru0.9Pt0.1O2/C was due to the change in the reaction mechanism from “adsorbate evolution” to “lattice participation”. Our findings increase the possibility of significantly overcoming the activity and stability limits of Ru-based electrocatalysts for the OER using Pt. Keywords: Water splitting, Oxygen evolution reaction, Ruthenium‑platinum oxide, in situ/operando ICP-MS, Lattice participation mechanism